2011
DOI: 10.1038/ng.776
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in ORC1, encoding the largest subunit of the origin recognition complex, cause microcephalic primordial dwarfism resembling Meier-Gorlin syndrome

Abstract: Studies into disorders of extreme growth failure (for example, Seckel syndrome and Majewski osteodysplastic primordial dwarfism type II) have implicated fundamental cellular processes of DNA damage response signaling and centrosome function in the regulation of human growth. Here we report that mutations in ORC1, encoding a subunit of the origin recognition complex, cause microcephalic primordial dwarfism resembling Meier-Gorlin syndrome. We establish that these mutations disrupt known ORC1 functions including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
238
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 190 publications
(255 citation statements)
references
References 22 publications
13
238
3
1
Order By: Relevance
“…In vitro studies using lymphoblastoid cell lines or skin fibroblast cell lines from two individuals with mutations in ORC1 showed reduced levels of ORC1, ORC2, and MCM2 in chromatin-enriched cell fractions. 13 Furthermore, the S-phase entry/progression in both individuals was delayed.…”
Section: Meier-gorlin Syndrome (Mgs) (Mim 224690mentioning
confidence: 99%
See 3 more Smart Citations
“…In vitro studies using lymphoblastoid cell lines or skin fibroblast cell lines from two individuals with mutations in ORC1 showed reduced levels of ORC1, ORC2, and MCM2 in chromatin-enriched cell fractions. 13 Furthermore, the S-phase entry/progression in both individuals was delayed.…”
Section: Meier-gorlin Syndrome (Mgs) (Mim 224690mentioning
confidence: 99%
“…13 As individuals with mutations in ORC1 showed overlapping features with MGS, mutation analysis of ORC1 was performed in 33 individuals with MGS and revealed mutations in 4 individuals from three families. 13 Mutation analysis of other genes of this prereplication complex showed mutations in ORC4, ORC6, CDT1, and CDC6 in 14 individuals from nine families with MGS. 14 Simultaneously, beginning with a family-based mapping approach in individuals with MGS with a founder effect, Guernsey et al 15 identified mutations in ORC1, ORC4, and CDT1 in eight individuals from five families with MGS.…”
Section: Meier-gorlin Syndrome (Mgs) (Mim 224690mentioning
confidence: 99%
See 2 more Smart Citations
“…Malheureusement il n'existe, pour l'heure, aucune cartographie de cette marque dans les cellules humaines qui puisse être comparée à la position des sites ORC. À noter que les mutations affectant le domaine BAH sont retrouvées chez des patients atteints du syndrome Meier-Gorlin, un syndrome rare qui se caractérise par une petite taille, de petites oreilles et des rotules sous-développées [33,34]. À n'en pas douter la cartographie des différentes formes méthylées de la lysine 20 de l'histone H4 sera une étape importante pour notre compréhension du mécanisme de sélection des origines de réplication.…”
Section: Comment Se Spécifient Les Origines De Réplication ?unclassified